Pembinaan Disiplin Siswa Pada Sekolah Menengah Kejuruan - Vikran Maulana; Nellitawati Nellitawati (Indonesian Counselor Association (IKI), 2020)
This purpose of research to see about discipline student coaching by the team of Gerakan Disiplin Sekolah in SMK Negeri 1 Sintuk Toboh Gadang Kabupaten Padang Pariaman. The population of the research was 899 students taken from the population using The Simple Random Sampling Technique. The total number of samples for this research was 90. The research uses the description of the quantitative method. The research instrument was a questionnaire in the form Likert Scale which five choices of answer that have been tested for validity and reliability by using application SPSS 16.0 version. The based on the research (1) discipline student coaching from giving an example by team GDS to the student is in a good enough category (2) discipline student coaching from giving punishment by team GDS to the student is in a good enough category (3) discipline student coaching from giving motivation by team GDS to the student is in a good enough category (4) discipline student coaching from supervision by team GDS to student is in a good enough category.